Foot shape assessment techniques for orthotic and footwear applications: a methodological literature review - Danckaers, Femke; Stanković, Kristina; Huysmans, Toon; Booth, Brian G.; Sijbers, Jan (Frontiers in Bioengineering and Biotechnology, 2024)
Foot shape assessment is important to characterise the complex shape of a foot, which is in turn essential for accurate design of foot orthoses and footwear, as well as quantification of foot deformities (e.g., hallux valgus). Numerous approaches have been described over the past few decades to evaluate foot shape for orthotic and footwear purposes, as well as for investigating how one's habits and personal characteristics influence the foot shape. This paper presents the developments reported in the literature for foot shape assessment. In particular, we focus on four main dimensions common to any foot assessment:(a) the choice of measurements to collect, (b) how objective these measurement procedures are, (c) how the foot measurements are analyzed, and (d) other common characteristics that can impact foot shape analysis. For each dimension, we summarize the most commonly used techniques and identify additional considerations that need to be made to achieve a reliable foot shape assessment. Finally, we present how different choices along these two dimensions impact the resulting foot assessment, and discuss possible improvements in the field of foot shape assessment.